NILAI MODERASI BERAGAMA PADA BUKU DIGITAL MADRASAH - , (Jurnal el-Huda, 2022)
The development of religious moderation through formal education in madrasas is expected to be part of a culture (school culture). For the purpose of building a culture, madrasas can implement several activities that shape the character of religious moderation. Religious moderation has become a major issue in recent years, not only included in the discussion in the political space but also in the realm of academic/educational discussions. This article aims to describe the values ​​of religious moderation in the Digital Book of Madrasah Tsanawiyah Fiqh Subject Class VIII Curriculum 2013. This research method uses a non-interactive qualitative approach with the type of library research (Library research). Data collection is done by analyzing documents, and for data analysis techniques using Content Analysis. The results of the study show that: There are values ​​of religious moderation in the books of class VIII fiqh students. Moderation values ​​include the value of Al-Ishlah (Wisdom Value), Muwathanah (Love the Motherland), I'tidal/proportionate attitude, Tasamuh (Tolerance), Qudwah (Exemplary Value), and Tahadhur (Civilized Value).